2022
DOI: 10.5935/0103-507x.20220024-en
|View full text |Cite
|
Sign up to set email alerts
|

Low T3 syndrome as a prognostic factor in patients in the intensive care unit: an observational cohort study

Abstract: Objective To assess euthyroid sick syndrome as a prognostic factor in patients in the intensive care unit; to detect factors that may affect mortality; and to develop an equation to calculate death probability. Methods This was a longitudinal, observational, nonconcurrent cohort study developed in the intensive care unit of Fundação Santa Casa de Misericórdia do Pará . One hundred adults with no prior documented endocrinopathy were submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…LT3S was considered an adaptative response to preserve energy in acute and chronic severe diseases ( 13 ). Accumulating evidence showed that LT3S was strongly associated with poor prognosis in critical illnesses ( 14 , 15 ). In the past few years, the interplay between LT3S and cardiovascular disease has attracted great attention ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…LT3S was considered an adaptative response to preserve energy in acute and chronic severe diseases ( 13 ). Accumulating evidence showed that LT3S was strongly associated with poor prognosis in critical illnesses ( 14 , 15 ). In the past few years, the interplay between LT3S and cardiovascular disease has attracted great attention ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%